(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The arguments border on importance and availability of connections between and the Nigerian society and journalism. In Nigeria literature and journalism tell about oppressions humans’ faces, especially in postcolonial African society where both are instruments of resistance against oppression. This paper combines the concepts and ideas of Nigerian press and its connection with the Nigerian society. Through the novel The Activist by Ojaide this paper will locate the place of journalists in Nigeria.